Diode Laser Spectroscopy of the Dynamics of Multiphoton Excitation of SF6 Molecules by CO2 Laser Pulses. Issue 2 (1988) - Kuritsyn, Yu. A.; Makarov, G. N.; Pak, I.; Sotnikov, M. V.; Zasavitsky, I. I.; Shotov, A. P.
Abstract : The dynamics of excitation by CO2 laser pulses of SF6 molecules from individual rotational sublevels J ″ of the ground vibrational state have been investigated in a pulsed molecular jet under essentially collisionless conditions. At different energy fluences of exciting laser pulse Φ = 10 −5 + 10 −1 J/cm 2, the dependences of the fractionf J of excited molecules on the rotational quantum number J ″ have been obtained, when SF6 molecules were excited on the 10P(16) CO2 laser line, as well as on the 10P(18) and 10P(14) lines at Φ = 0.1 J/cm 2 . Comparison of experimental results with theoretical predictions 18–20 shows rather strong disagreement between theory and experiments both in the population of the υ3 = 1 state and in the role of multiphoton transitions. It is shown that the narrowing of the exciting laser pulse spectrum (the 10P(16) line, Φ ≲ 10 −2 J/cm 2 ) results in drastic decrease of the fraction of excited molecules from the (υ3 = 0, J ″ = 4) state which is most resonant with laser radiation.